First report of Rhizoctonia solani Kühn AG 2-2 LP in Zoyzia japonica Steud in Brazil - Picarelli,Maria Aurea Saboya Chiaradia (2020)
ABSTRACT The use of cultivated grasses in Brazil has grown by 40% between 2010 and 2015, and the species Zoysia japonica Steud, especially the cultivar ‘Esmeralda’, corresponds to 81% of the grass market in the country. The most important disease affecting zoysia grass, known as large patch, is caused by Rhizoctonia solani and occurs in the Brazilian lawns particularly during winter months. The aim of this study was to contribute to the identification and characterization of the anastomosis group of R. solani isolates from lesions typical of large patch collected from ‘Esmeralda’ grass at gardens and golf courses in the states of São Paulo and Bahia, Brazil. All 12 obtained isolates presented dark-brown colonies with aerial mycelial growth, multinucleated hyphae and absence of concentric zonation or sclerotia, and showed their greatest mycelial growth rate at 25°C. In pathogenicity experiments, except three out of R. solani isolates, reduced the growth of zoysia grass. Based on the analysis of sequences of the rDNA-ITS region, the isolates clustered with reference isolates of the anastomosis group AG 2-2 LP. Phylogenetic inference showed that the Brazilian isolates are grouped into two clades that shared the same common ancestral with 96% bootstrap. One of the clades includes only Brazilian isolates while the other one also includes American and Japanese R. solani isolates AG 2-2 LP. This is the first report and characterization of R. solani AG 2-2 LP in zoysiagrass in Brazil.